2020
DOI: 10.1159/000510658
|View full text |Cite
|
Sign up to set email alerts
|

Creatinine at Birth Correlates with Gestational Age and Birth Weight: Another Factor of the Imbroglio in Early Neonatal Life

Abstract: <b><i>Background:</i></b> Serum creatinine (S<sub>cr</sub>) in early neonatal life (first week of life) displays extensive variability; hence, a better understanding is needed to use S<sub>cr</sub> as a diagnostic biomarker for acute kidney injury (AKI). <b><i>Objective:</i></b> The objective of this study was to explore S<sub>cr</sub> trends and its covariates in early neonatal life. <b><i>Methods:</i></b&… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 10 publications
5
8
0
Order By: Relevance
“…In both data sets, we noticed a similar pattern with an initial increase from birth onwards over the first day of postnatal life and a subsequent decline after the first day of postnatal life, confirming the patterns earlier described in other cohorts of (near)term neonates [52][53][54].…”
Section: Resultssupporting
confidence: 89%
“…In both data sets, we noticed a similar pattern with an initial increase from birth onwards over the first day of postnatal life and a subsequent decline after the first day of postnatal life, confirming the patterns earlier described in other cohorts of (near)term neonates [52][53][54].…”
Section: Resultssupporting
confidence: 89%
“… Creatinine level in the amniotic and fetal fluids. (A) Fetal amniotic creatinine concentration as a function of fetal age, (B) weighted means (circles) and SD of amniotic creatinine level plotted against Fetal age, (C) Amniotic creatinine concentration against predicted FUPR based on the function derived from 3D data (D) reported references values for the creatinine in fetal urine from fetuses diagnosed with ( 6 , 48 ) and without ( 49 ) urinary tract uropathies (E) Fetal amniotic to urine creatinine ratio, and (F) Serum creatinine in maternal serum [lines ( 50 )] overlaying measured neonatal serum creatinine at birth [squares ( 51 )]. Solid and broken lines represent the median and 5th-95th intervals.…”
Section: Resultsmentioning
confidence: 99%
“…Data were generated using this function assuming 25% CV and then compared against 4,509 SerCr measurements obtained at birth (23–42 GAs) from 1,181 newborns ( 51 ). Due to its low molecular weight (113.12 g/mol), creatinine freely passes the placental barrier and its level at birth is known to reflect the maternal level.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Creatinine and uric acid were generally considered to be associated with kidney function. It was reported that neonatal creatinine could reflects the level of maternal renal function ( 26 ), and predict the onset of neonatal acute kidney injury to some extent ( 27 ). Uric acid have effects on fetal growth and kidney development, and lead to a tendency of low-birth-weight infants ( 28 ).…”
Section: Discussionmentioning
confidence: 99%